Two new species of Domene Fauvel, 1873 (Coleoptera: Staphylinidae: Paederinae) from Portugal and faunistic notes - Serrano, Artur R.m.; Aguiar, Carlos A.s. (Zootaxa, 2025)
Two new species of rove beetles belonging to the genus Domene Fauvel, 1873, subgenus Lathromene Koch, 1938 from Portugal are described: Domene (Lathromene) boavidae sp. nov. and Domene (Lathromene) pedroi sp. nov. These subterranean species are diagnosed and compared with closely related species from the Iberian endemic subgenus Lathromene. The external morphology and male genitalia are illustrated and information on the species` ecology is presented. A dichotomous key for identifying species of the Lathromene subgenus, based on male genitalia, is presented. New faunistic and ecological data on Domene (Lathromene) viriatoi Serrano & Boieiro, 2015 are also given.